A Practical guide to HPLC detection - Parriott, Donald (Academic Press, 1993)
This guide for the practicing chromatographer who wants a ready source of information on HPLC detection explores and compares existing detection systems and detectors, outlines the common problems associated with a given detector, and offers proven approaches to avoiding such problems. Key Features * Addresses the practical aspects of HPLC detection, including: basic theory * when a particular type of detector can be used * how detectors from various manufacturers differ * common problems of detectors and ways to avoid them * Presents an overview of today's most common techniques * Discusses the advantages and disadvantages of HPLC, dispelling common misconceptions.